Influence of crystalline defects on nitrogen implantation in copper for surface hardening. (1st July 2023) - Zaher, Ghenwa; Sauvage, Xavier; Jouen, Samuel
Abstract: The design of electrical contacts that combine a high electrical conductivity and excellent wear resistance requires the optimization of surface processing. Surface hardening of copper was achieved by nitrogen implantation and the underlying mechanisms were investigated by electron microscopy. Pure copper and a CuSn alloy were implanted with nitrogen in the recrystallized state and after severe plastic deformation. The larger lattice parameter of CuSn does not promote the implantation of N but the large density of crystalline defects in the as-deformed material gives rise a much thicker implanted layer up to 120±20 nm. In all cases, the strong hardening results from a high density of nanoscaled Cu3 N particles (1.2 ± 0.4 10 23 m −3 ). Deformation twins seem to promote both the diffusion and the nucleation of Cu3 N. Graphical abstract: Image, graphical abstract